Mitigation of greenhouse gas and reactive nitrogen from the Japanese passenger car fleet. (20th December 2020) - Xue, Mianqiang; Wang, Qun; Lin, Bin-Le; Tsunemi, Kiyotaka
Abstract: Policies tackling target environmental impacts can affect other aspects of environmental quality adversely or beneficially, which brings about questions on trade-offs or co-benefits. The passenger car fleet contributes an important part of total emissions driving concerns on both climate change and nitrogen cycle disturbance. In the present study, we investigated simultaneously the time series greenhouse gas and reactive nitrogen emissions of the Japanese passenger car fleet from a life cycle perspective. The integrated model which consists of the dynamic material flow sub-model and life cycle analysis sub-model was used for the analysis. The results indicated that the stock of passenger cars had a relatively small variation at approximately 50 million yet with rapid evolving stock composition from 2000 to 2030, which resulted in a change in energy consumption structure. The emission of greenhouse gas achieved a reduction of 35% by 2030 compared to 2005. Remarkably, the emission of reactive nitrogen was reduced by 66% within this same period. The greenhouse gas emission is mainly stemmed from the Tank to Wheel (TTW) stage. As for reactive nitrogen, the emission from TTW stage was higher than that from Well to Tank (WTT) stage from 2000 to 2013, whereas it reversed from 2013 to 2030. Finally, policy implications were presented based on energy consumption structure change, mitigation effort shift and contribution of key pollutant species. Highlights: Evolving car stock composition lead to energy consumption structure change. Both the greenhouse gas and reactive nitrogen were reduced successfully. A changed major source for reactive nitrogen was identified. Policy implications from different perspectives were presented.